2019
DOI: 10.1186/s12992-019-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened beverage affordability and the prevalence of overweight and obesity in a cross section of countries

Abstract: Background A key component of ‘obesogenic environments’ is the ready availability of convenient, calorie-dense foods, in the form of hyper-palatable and relatively inexpensive ultra-processed products. Compelling evidence indicates that the regular consumption of soft drinks, specifically carbonated and non-carbonated sugar-sweetened beverages (SSBs), has a significant impact on the prevalence of overweight and obesity. However, to implement country-level effective prevention programmes we need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
2
49
0
7
Order By: Relevance
“…In our study, more than two thirds of those who reported a reduction in SSB consumption stated the increase in price as a reason for change, like in Hungary [39]. Hence, being affordability a major driver of SSB purchasing behaviours [40], while targeting manufacturers may increase public support for the tax, like in the UK [23], its potential effect on SSB consumption can be comprised if the tax is not fully passed to consumers. Our data on SSB prices show that the tax was passed through to consumers, with 8.3% for small-sized containers and 17.5% for large-sized containers, using the change in prices in Madrid over the same period as reference for comparison purposes.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, more than two thirds of those who reported a reduction in SSB consumption stated the increase in price as a reason for change, like in Hungary [39]. Hence, being affordability a major driver of SSB purchasing behaviours [40], while targeting manufacturers may increase public support for the tax, like in the UK [23], its potential effect on SSB consumption can be comprised if the tax is not fully passed to consumers. Our data on SSB prices show that the tax was passed through to consumers, with 8.3% for small-sized containers and 17.5% for large-sized containers, using the change in prices in Madrid over the same period as reference for comparison purposes.…”
Section: Discussionmentioning
confidence: 86%
“…Scientific evidence supports the strong association between UPF consumption and the risk of developing Non-Communicable Diseases (NCDs), especially obesity [ 5 , 6 , 7 , 8 , 9 ]. The prevalence of these conditions increases directly as the consumption of UP and UPF surges [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained from the demographic and epidemiological transitions with increasing life expectancy, an ageing population and the subsequent burden of chronic diseases [18,[26][27][28][29][30][31]. Not only are many people now living with chronic communicable diseases which previously were fatal, but there is also an increasing prevalence of non-communicable diseases which are lifestyle-related and/or come as complex, multiple co-morbidities resulting in varying types and degrees of long-term disabilities [1,13,[32][33][34][35][36][37][38][39][40][41]. Rehabilitation is required to attenuate the effects of disability and optimize functioning in people with functional limitations from any health condition [25,42].…”
Section: Introductionmentioning
confidence: 99%